Study on Energy Dissipation Characteristics and Damage Law of Backfill under Cyclic Impact - Xianglong Li; Qinglian Zhou; Jianguo Wang; Wei Sun; Yongxin Yao; Yongbo Wu; Zhiping Zhang (Shock and Vibration)
This research aims to study the damaging effect of underground blasting mining pillars on adjacent cemented filling bodies. The filling bodies were made by mixing ore rock with ash sand by the ratio of 1 : 4 and 1 : 6, respectively, which were subjected to cyclic impact tests with the split-Hopkinson pressure bar under the pressure of 0.2 MPa and 0.24 MPa to analyze the energy dissipation characteristics and damage law. The results showed that as the stress wave induced by the cyclic impact was transmitted to the composite specimen, the energy was absorbed for crack growth and development. Then, the energy reflection ratio increased while the energy dissipation ratio and transmission ratio decreased. For the combined specimen with the cement-sand ratio of 1 : 4, after five cycles of impact under the condition of Ip = 0.2 MPa, the damage variables were 0.07, 0.11, 0.51, and 0.56, respectively, since the second time; under the condition of Ip = 0.24 MPa, the damage variables were 0.17, 0.29, 0.55, and 0.66, respectively. After reaching the damage threshold of 0.63, the damage variable showed nonlinearity. Moreover, it was found that the mechanical properties of the filling body affect the whole combined specimen, and the dynamic strength of the combined specimen with the cement-sand ratio of 1 : 4 was higher than that of the cement-sand ratio of 1 : 6. Therefore, it can be concluded that during the two-step pillar recovery, the amount of blasting explosive can be appropriately reduced, and the number of blasting can be increased to reduce the damaging effect of blasting impact on the cemented pillar and reserved pillar to maintain stability.